Interactions between cortisol and lipids in human milk - Kaisa M. Linderborg; Maaria Kortesniemi; Anna-Katariina Aatsinki; Linnea Karlsson; Hasse Karlsson; Baoru Yang; Henna-Maria Uusitupa (BMC, 2020)
Abstract Background Human breast milk is one of the key early postnatal biological exposures for the developing child. It includes bioactive compounds, such as cortisol and fatty acids, which may be linked via the mother's lipid metabolism. Methods This study investigated the associations between cortisol and lipids in human milk at the infant age of 2.5 months. Human milk cortisol concentrations were measured using luminescence immunoassay, and two groups of milks (n = 50 each) were formed based on either high (> 10 nmol/L) or low (< 3 nmol/L) cortisol levels. Lipids, as fatty acid content and composition of neutral (triacylglycerol-rich) and polar (phospholipid-rich) lipids, were measured with gas chromatography. The samples originated from the FinnBrain Birth Cohort Study. Results The percentage of phospholipid-rich lipids of total lipids was 33.08% ± 1.33%. In triacylglycerol-rich lipids, high cortisol level in milk was associated with higher lauric (12:0, mass % and mg/mL), myristic (14:0, mass % and mg/mL), eicosenoic (20:1n − 9, mass %), docosenoic (22:1n − 9, mass %, and mg/mL) acids, and to lower palmitic acid (16:0, mass %) compared with low cortisol levels in milk. In phospholipid-rich lipids, high cortisol level was associated with higher myristic (14:0, mass %) and docosenoic (22:1n − 9, mass %) acids. After adjusting for pre-pregnancy BMI and sampling time by linear regression, the milk cortisol remained a significant predictor for lauric and myristic acids in triacylglycerol-rich lipids, and myristic and docosenoic acid in phospholipid-rich lipids (β = 0.23 to 0.38 and p < 0.05 for each). Conclusions This study revealed certain significant associations between milk cortisol and the fatty acid composition of human milk, indicating that cortisol might be one of the factors affecting the origin of the lipids in human milk.